Competencies for integrating Sustainable Development Goals (SDGs) of Chinese and English language teachers in Shandong Province, China - Wang, Cong; Syed Abdullah, Sharifah Intan Sharina (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines and compare the competencies of Chinese and English language teachers in integrating Sustainable Development Goals (SDGs) within their teaching practices in Shandong Province, China. Utilizing a quantitative research design, a questionnaire survey was conducted among 768 teachers from primary and secondary schools. The analysis focused on seven key areas of pedagogical content knowledge (PCK) relevant to SDG integration, which are knowledge of subject matter, knowledge of curriculum, knowledge of learner, knowledge of instructional strategies, knowledge of context, knowledge of educational goals, and knowledge of assessment. Descriptive statistics and t-tests were used to compare the competencies between the teachers of two languages. The findings indicate that English language teachers exhibit higher proficiency in knowledge of curriculum, knowledge of instructional strategies, and knowledge of assessment, whereas Chinese language teachers demonstrate a stronger understanding of SDG-related subject matter. These differences highlight the need for targeted professional development to enhance teachers' capabilities in integrating SDGs into their teaching. The study underscores the importance of providing adequate resources, training, and institutional support to foster sustainable development education, ultimately preparing students to become informed and responsible global citizens.